1996
DOI: 10.1021/es9504505
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Bacteria in Marine Waters for the Distribution of Hydrophobic Organic Contaminants

Abstract: Pelagic bacteria represent the potentially most predominant biological, particulate sorptive surface for hydrophobic organic contaminant (HOC) and constitute a food source for the microheterotrophic food web, which conceivably continues up to pelagic fish. However, no data have been reported on HOCs in bacteria. Therefore, this fraction (0.2-2 µm) was isolated with a new technique in situ in the Baltic Sea followed by HOC analysis (HRGC-MS). Results show bacterial concentrations (PAHs and PCBs) in the same ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Several laboratory and field studies have reported BAFs (organic carbon normalized) higher than KOW (45,47,48), indicating greater partitioning of PCBs into organic carbon than octanol.…”
Section: Resultsmentioning
confidence: 99%
“…Several laboratory and field studies have reported BAFs (organic carbon normalized) higher than KOW (45,47,48), indicating greater partitioning of PCBs into organic carbon than octanol.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have focused on the fate and transport of these chemicals (Moon et al 2003, Palm et al 2004 and application of remedial technologies to manage those (Iturbe et al 2004, Chaudhry et al 2005, Trably & Patureau 2006. Due to the different intrinsic physicochemical properties of individual PAHs, such as solubility, vapor pressure and lipophilicity, they tend to interact to different extents with sediments, SPM, and biota (Broman et al 1996 1997, Zhou & Maskaoui 2003), and are subject to various transformation processes including chemical transformation, biodegradation and photochemical degradation. The partitioning of PAHs between sediment and water at equilibrium has been widely considered as a partitioning process (Karickhoff et al 1979, Means et al 1980, where dissolved organic carbon (DOC) and particulate organic carbon (POC) have also been suggested to play an important role in controlling the fate of the hydrophobic compounds in aquatic systems (Mitra & Dickhut 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There are indications that the Bothnian Bay is dominated by bacterial production that may play an important role in the accumulation of dioxins and affect their levels up to fish (Broman et al 1996, Wallberg et al 1997. The latter authors pointed out that in present risk assessments such pathways are not considered, likely leading to underestimated contamination at higher trophic levels.…”
Section: Sorption and Desorption On Particles And Dissolved Substancesmentioning
confidence: 99%